Mechanism for the Inhibition of α-Glucosidase by Peptide Tyr-Pro-Ile-Trp (YPIW) and Its Stability - TAO Qiang, LI Jiao, CAO Wanxue, CHEN Naidong (Shipin Kexue)
In order to investigate the inhibitory effect of a novel bioactive peptide, Tyr-Pro-Ile-Trp (YPIW), on α-glucosidase, a variety of analytical methods including enzyme inhibition kinetics, ultraviolet (UV) absorption spectroscopy and Fourier transform infrared spectroscopy (FTIR) were employed to investigate the underlying inhibitory mechanism. Besides, the stability and cytotoxicity of YPIW were evaluated. The results indicated that YPIW exerted a significant inhibitory effect on α-glucosidase (half maximal inhibitory concentration (IC50) = 1.03 mmol/L), which was comparable to that of acarbose (IC50 = 1.08 mmol/L). In the mixed competition mode, YPIW could reversibly inhibit the activity of α-glucosidase, and was more likely to bind with free α-glucosidase. The UV and FTIR showed that YPIW interacted with α-glucosidase, potentially altering the conformation of the enzyme, thereby reducing its catalytic activity. YPIW remained stable at low temperatures or in acidic environments, and had good tolerance to simulated gastrointestinal digestion. In addition, it had no obvious toxic effect on HepG2 cells in the concentration range of 0–1 mmol/L. This study provides a theoretical basis for the development of YPIW as a novel hypoglycemic peptide.